Interventions - Miles, Malcolm; Hall, Tim, 1968- (Advances in art & urban futures ;, 2005)
Interventions is a contribution to current considerations of how cultural initiatives and interventions affect the development of cities. It draws together policies and projects for cultural urban interventions, from the UK, Lithuania, India, and North America. The authors include artists, arts managers, academics in cultural and geographical fields, and policy makers. The book has three sections: the first on policies and strategies for cultural intervention; the second on specific projects (a set of case studies); and the third includes two important research reports evaluating public art an.